Random Walk of Stock Prices: A Test of the Variance-Time Function - Young, William E. (Econometrica, 1971)
[The relationship between the time interval over which changes in a random variable are measured, and the variances of the changes for various intervals are examined with a view toward testing the independence of stock price changes. A statistical test is presented and subsequent analysis of changes for 1, 2,..., 12 month intervals suggests that prices do exhibit nonrandom behavior and in such cases the propensity is toward price reversals]